Pengembangan Buku Praktik Pencak Silat Model Buku Bergambar bagi Siswa SD sebagai Upaya Pelestarian Budaya - Musran, Musran; Syahrianursaifi, Syahrianursaifi; Kurniawan, Erizal; Husaini, Husaini (Jurnal Porkes, 2024)
This study aims to produce a product of a martial arts practice book in the form of a picture book as a teaching material for the Physical Education subject in elementary schools. This study uses the R&D method with a model developed by Borg and Gall with 10 stages of the process. The stages begin with determining the problem, design, testing, and production. This study involved students and teachers in Banda Aceh. The subjects in this study were students and teachers of Physical Education at SD Negeri 45 Banda Aceh. The object developed was a martial arts practice book. The results of the study showed that (1) The results of the product trial concluded that the martial arts practice book received a score of 96% in the media/design aspect and a score of 92 in the material aspect. Based on this trial, it can be concluded that the product produced is very feasible to be developed. (2) The results of the trial of use on students and teachers also received scores in the very good category. The level of practicality of the martial arts practice book received a percentage of 89.7% based on student responses with a very feasible category. Meanwhile, the practicality level based on teacher responses received a score of 90.3% with a very feasible category. (3) This illustrated book model of martial arts practice book has various advantages from the media and materials in it. The book is well designed according to the visualization needed by elementary school students.